The significance study of Ar Rahn's operations towards their customer's needs: a case on Kota Bharu's outlet / Mohd Azmi Yahya - Yahya, Mohd Azmi (2000)
This research done as one way on determines and acceptance and what the customers needs toward the product. The product that had mentioned here is Islamic Pawn product offered by Ar Rahn. Pawn or leasing is not only famous among lower class people but it becomes of all peoples next in this millenium. And many organizations offer their product in order to fulfill the customers needs. As a result of abovementioned problem, I think this is the right time for me to take these opportunities in attempting to solve the entire puzzle. Ar Rahn Kota Bharu had been selected in answering the above question. Islam not only offered to its believer the religion matters but also it's in fact the way of life. Business for example of how Islam put Syarak and syariah as its guideline in order to make sure all Muslim can achieved their goal. From this research I found that most of the people are well known about this product. It's including Muslim and non-Muslim. But the level of acceptance is largely different. At the same time the management of Ar Rahn should think over about their service offer to the customers.